2013
DOI: 10.1063/1.4801950
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric permittivity enhancement in hydroxyl functionalized polyolefins via cooperative interactions with water

Abstract: Recent experiments have shown that polypropylene (PP) with a small fraction of hydroxyl (-OH) side groups displays a two-fold increase in the dielectric permittivity. It has been suggested that both the -OH groups and trapped water molecules may contribute to the dielectric constant increase. In this first principles computational study, using short polyolefin chains as models of PP, we shed light on the role played by -OH functional groups and the trapped moisture. Our results reveal that the trapped water mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
8
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 21 publications
2
8
0
Order By: Relevance
“…Similar observations were made for the PPOH-x copolymers with lower hydroxyl concentration (results not shown). H-bonded and non H-bonded O-H stretching peaks from bound and free water also occur in this spectral region,21 so the 210 cm -1 shift of the Hbonded O-H stretching from 3332 cm -1 at 23C to 3542 cm -1 at 250C may also be due, in part, to the loss of bound water from the PPOH copolymer. Strain sweeps at 200C and  = 1 rad/s (see supplementary information) indicated that the linear viscoelastic behavior (LVE) of PP was maintained until about 31% strain, and the linear range limit decreased for the PPOH copolymers to about 13% for PPOH-3.9.…”
mentioning
confidence: 98%
“…Similar observations were made for the PPOH-x copolymers with lower hydroxyl concentration (results not shown). H-bonded and non H-bonded O-H stretching peaks from bound and free water also occur in this spectral region,21 so the 210 cm -1 shift of the Hbonded O-H stretching from 3332 cm -1 at 23C to 3542 cm -1 at 250C may also be due, in part, to the loss of bound water from the PPOH copolymer. Strain sweeps at 200C and  = 1 rad/s (see supplementary information) indicated that the linear viscoelastic behavior (LVE) of PP was maintained until about 31% strain, and the linear range limit decreased for the PPOH copolymers to about 13% for PPOH-3.9.…”
mentioning
confidence: 98%
“…The strategies of polymer-based dielectric research via QCC are reviewed by Wang et al [ 364 ]. In this work, focus is on the typical DFT calculations used to determine the properties of dielectrics, such as the dielectric constant and band gap by Wang et al [ 365 ]. Nowadays, biaxially oriented polypropylene (PP) is the most common dielectric used for high-energy-density capacitors, but the dielectric constant is low.…”
Section: Case Studies For Connection Of Computational Chemistry and Kinetic Modelingmentioning
confidence: 99%
“…4 The current industrial standard, biaxially-oriented polypropylene (BOPP), has a dielectric constant of ~2.2 across a broad frequency range, low dielectric loss (~1x10 -4 ) and a breakdown strength of ~700MV/m. 5 Other efforts to achieve high energy density in dielectric materials are focused on PVDF composites, 6,7 aromatic polyureas and polythioureas, 8,9 hybrid organic/inorganic composites, 10 and the functionalization of polypropylene, 11,12 among others. 13 In line with other research in our group, 14,15,16 we seek to increase the dielectric constant of materials by the inclusion of electronegative atoms into the polymer backbones.…”
Section: Introductionmentioning
confidence: 99%